2012
DOI: 10.4236/ojvm.2012.22010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mast Cells in Dermal versus Subcutaneous Hemangiomas and Hemangiosarcomas in Dogs

Abstract: This study investigated the role of mast cells in canine cutaneous vascular tumors, and is the first such study to distinguish between tumors arising in the dermis versus the subcutis. Mast cell numbers in canine cutaneous hemangiomas (HA) and hemangiosarcomas (HSA) were evaluated to identify a relationship between mast cells, tumor type (HA, HSA), histologic location (dermis, subcutis) and tumor recurrence. One hundred and sixty-seven biopsies from 148 dogs were evaluated. Using only one biopsy from each dog,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…In dogs generally solar radiation is a contributing factor in the development of several skin neoplasms including haemangiomas and hemangiosarcomas (Gross et al, 2005). Barber et al, (2012) reported histologically the hemangioma was appearing well circumscribed masses composed of discrete vascular structure lined by single layer of flattened endothelial cells arranged on fine collagenous septa and filled by erythrocytes which is similar to our histological findings. Lather et al, (2015) reported haemangioma on left flank abdominal region while Kim et al, (2005) reported on right dorsal antebrachium and on the right shoulder in mixed breed spayed female which removed surgically while Balachandran et al, (2014) reported cavernous haemangioma in three year old Rajpalatyam dog at chest region and removed surgically.…”
Section: Treatment and Discussionsupporting
confidence: 91%
“…In dogs generally solar radiation is a contributing factor in the development of several skin neoplasms including haemangiomas and hemangiosarcomas (Gross et al, 2005). Barber et al, (2012) reported histologically the hemangioma was appearing well circumscribed masses composed of discrete vascular structure lined by single layer of flattened endothelial cells arranged on fine collagenous septa and filled by erythrocytes which is similar to our histological findings. Lather et al, (2015) reported haemangioma on left flank abdominal region while Kim et al, (2005) reported on right dorsal antebrachium and on the right shoulder in mixed breed spayed female which removed surgically while Balachandran et al, (2014) reported cavernous haemangioma in three year old Rajpalatyam dog at chest region and removed surgically.…”
Section: Treatment and Discussionsupporting
confidence: 91%